Photochromism in Fulgides and Anhydrides - S. Deshmukh, Sujata; Banerjee, Shubhra (Asian Journal of Chemistry, 2010)
Fulgides (1) and anhydrides (2) obtained from the products of Stobbe condensation, were irradiated when a photochemical change was observed showing their pholochromic nature.